Peningkatan Promosi Lembaga Pendidikan Melalui Pendampingan Pembuatan Website Sekolah - Khotim Fadhli; Tholib Hariono; Agus Sifaunajah; M Farid Nasrulloh; Ahmad Qomarudin Ahsan; Muhammad Kholil Asy’ari; Arjuna Andriyanto Cahyo Nugroho (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
Utilization of information technology is urgently needed to keep up with the rapidly changing times, one of which is the distribution of information that can be accessed quickly and easily by everyone via the internet. The existence of this information is also expected as part of the promotion of the achievements achieved by the agency or organization, as part of the existence of the agency or organization. The existence of an organization is also influenced by the advanced use of information technology by the organization, one of which is the use of the website. School is one of the educational organizations that would be able to develop a website. With the presence of a website in schools, it will help convey school information to the public, which can indirectly increase the credibility of the school in the eyes of the community in its seriousness to improve the quality of education. Promotion improvement through Assistance in Making School Websites at SDN Dukuharum is carried out through several stages, namely design, implementation, and evaluation. Through assistance in the creation of a school website, which was created with this partner, it has an influence on increasing the promotion of SDN Dukuharum, so that it can also have an impact on increasing its achievement. Partners have high enthusiasm in the process of assisting the creation of school websites as promotional media. The impact of this assistance is that teachers and staff are able to operate the website that has been created. so that when the implementation of community service is complete, partners can independently operate the website. Partners through the use of the school's website can carry out public services at SDN Dukuharum in a more modern way and can continue to increase the credibility of the agency by utilizing the management information system. Keywords: mentoring, website creation, promotion